Errant counterpublics : 'Solidarność' and the politics of the weak - Majewska, Ewa (2022)
The essay discusses the notion of counterpublics in the context of the creation of the Solidarność labour union in Poland in 1980. The proposed reading of these events not only offers a feminist recontextualization against the grain of Western liberal triumphalism, but furthermore explores the implications of postcolonial thought for the analysis of the recent history of a Central European country as well as for the discussion concerning the public spheres of the excluded and marginalized. The thought of Eduard Glissant, as well as that of Gloria Anzaldua and Gayatri Spivak, allows for a rethinking of these events and theories in a global perspective, thus facilitating a universalizing practice based on a particular, localized experience.